KEMAMPUAN LEADPRENEURSHIP KEPALA SEKOLAH - Ula, Naila Kholisotul (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
The implementation of leadpreneurship skills by the school principal is highly suitable for the needs of SMAN 1 Kalidawir Tulungagung, located in the outskirts. Based on the research activities conducted, the results can be summarized as follows, (1) the implementation of leadpreneurship concepts is evident in various activities, including the school principal's confident decision-making attitude, utilization of natural and human resources (teachers and students), double-track financial management, attentive listening to members' grievances and fostering familial relationships, considering every task as an act of worship and continuously motivating members, strengthening brotherhood ties and fostering both internal and external relationships, as well as integrating democratic, authoritarian, and paternalistic leadership styles, (2) improvement in teacher performance is observed through their participation in training activities (Law no. 14 of 2005, Article 14, Paragraph 11), active involvement in teacher organizations (MGMP), internal and external relationship building, moral, material, and facility completeness motivation, and compliance with expressing opinions in decision-making processes and adherence to final decisions, (3) the impact of the school principal's leadpreneurship skills on the quality of learning is evident in the teachers' varied delivery of classroom material, creation of conducive learning environments, student participation in various extracurricular activities (though still relatively low), alignment of delivered material with government policies and customization of material delivery based on each teacher's creativity, as well as the alignment of the learning system with the school's vision and mission, continuously enhancing the quality of the double-track program.